Challenges of inserting graduates of the Licentiate Degree in Rural Education in a teaching profession - Janata, Natacha Eugenia; Correa, Antony Josue [UNESP]; Stefanes, Katila Thaiana (Univ Federal Tocantins, Campus Tocantinopolis, 2021)
In this study, we made reflections of the challenges from inserting graduates into the teaching profession of the aforementioned course at the Universidade Federal Santa Catarina. We developed bibliographic research on the teaching work and the graduation project of this degree, document analysis, data collection with field research, of an exploratory nature, and the data gathering using a questionnaire. The results, still partial, indicate as limiting aspects: the non-inclusion of the qualification of a Licentiate Degree in Educacao do Campo (Rural Education) in qualifying processes, the refusal of the graduate by the educational council and/or institutions, or being hired as non-qualified. Some situations were reversed by dialogue and appeals to public notices, an aspect considered as an enhancement. As a contradictory and emerging element to the debate, there is a restriction of the diploma and the job duties being valid only for rural schools. Advancing on the discussions about the degree and insertion in the teaching profession, we pointed out the relevance of the collective organization of the graduates through the movements that fights for Rural Education. Necessary improvements for the transformation of schools and for the future horizon.
Keywords: Teaching profession/work; Degree in rural education; Professional insertion